Diseño y aplicación de una guía de juegos dirigidos para fortalecer el desarrollo socio afectivo en niños y niñas de primer año de educación básica paralelo “A” de la escuela 9 de Octubre del cantón Pujilí, parroquia La Matriz, provincia de Cotopaxi en el año lectivo 2013- 2014 - Anchatipán Espín, Jenny Elizabeth (2015)
At the stage of childhood conflicts are evidenced when children start the nursery school, since the change of the family environment to educational causes difficulty in adapting to this new environment, so it is important the cares, provided by parents, teachers and relatives; as a child needs of these elements in order to achieve their full development being the main axis for the good performance of the infant, knowing that the environment of the child is essential for transmitting the first lessons. In childhood all their skills must be promoted, this is the right moment where the plasticity of the brain is like a sponge that absorbs all the knowledge in order to establish a systematic review of all educational areas such as: the psychomotor, intellectual, language and of course the socio- affective; where the adults either in their role as parents or teachers act as mediators. It is fair to note that the game is a strategy that leaves a big knowledge and therefore experiences that will be useful for the evolution of the child and this will help to the integration and the better socialization between classmates since the beginning of the school year the infants are shy, aggressive and it is hard to practice values such as respect, solidarity and friendship characteristics of this age....